Sex Disparities in the Association of Serum Uric Acid With Kidney Stone: A Cross-Sectional Study in China - Xu, Jin-Zhou; Lu, Jun-Lin; Hu, Liu; Xun, Yang; Wan, Zheng-Ce; Xia, Qi-Dong; Qian, Xiao-Yuan; Yang, Yuan-Yuan; Hong, Sen-Yuan; Lv, Yong-Man; Wang, Shao-Gang; Lei, Xiao-Mei; et al. (Frontiers in Medicine, 2022)
Background & Aims: Urolithiasis is characterized by high rates of prevalence and recurrence. Hyperuricemia is related to various diseases. We hope to determine the association between serum uric acid level and kidney stone. Methods: In this population-based cross-sectional study, a total of 82017 Chinese individuals who underwent a comprehensive examination in 2017 were included. The kidney stone was diagnosed based on ultrasonography examination outcomes. Fully adjusted odds ratio (OR) for kidney stone, and mean difference between two groups were applied to determine the association of uric acid level with kidney stone. Results: Among the 82017 participants included in this study (aged 18~99 years), 9435 participants (11.5%) are diagnosed with KS. A proportion of 56.3% of individuals is male. The mean UA level of overall participants is 341.77 μmol/L. The participants with KS report higher UA level than the participants without KS (mean UA level 369.91 vs. 338.11 μmol/L; mean difference (MD), 31.96 [95% confidence interval, CI, 29.61~34.28] μmol/L). In males, the OR for KS significantly increases from 330 μmol/L UA level. Every 50 μmol/L elevation of UA level increases the risk of KS formation by about 10.7% above the UA level of 330 μmol/L in males. The subgroup analysis for male is consistent with the overall result except for the participants presenting underweight (adjusted OR, 1.035 [0.875~1.217]; MD, -5.57 [-16.45~11.37]), low cholesterol (adjusted OR, 1.088 [0.938~1.261]; MD, 8.18 [-7.93~24.68]) or high estimated glomerular filtration rate (adjusted OR, 1.044 [0.983~1.108]; MD, 5.61 [-1.84~13.36]). However, no significant association is observed in females between UA and KS either in all female participants or in female subgroups. Conclusion: Among Chinese adults, uric acid level is associated with kidney stone in a dose-response manner in males but not in female. However, the association becomes considerably weak in male participants with malnutrition status.